E-learning user interface design for lecturers based on usability scale system approach (Case Study: E-Learning Universitas Muhammadiyah Magelang) - Iqbal Ridwan Darmawan; Purwono Hendradi; Pristi Sukmasetya (Universitas Muhammadiyah Magelang, 2022)
Universitas Muhammadiyah Magelang provides an online learning service portal through an e-learning website MOCA. However, the low level of use of the MOCA website and the usability problems that usually arise in MOCA, indicate the need for usability testing. Usability testing is carried out to measure usability aspects, namely: effectiveness, efficiency, and user satisfaction. This study used a System Usability Scale questionnaire which was tested on 61 lecturers. This study aims to measure usability aspects according to the user's subjective assessment. The results of the study can describe the level of usability of MOCA from the user's point of view. the results of the MOCA usability test using the SUS method got a score of